Studies on water resources salinization along the Italian coast: 30 years of work - Micòl Mastrocicco (Acque Sotterranee, 2021)
The population density on the Italian coasts is twice the national average. Numerous urban, economic, and productive settlements lie along the coast, which in many areas have altered the natural characteristics of the territory. Moreover, recent climate change studies forecast large impacts on the hydrologic cycle in the Mediterranean. Thus, in the next years, coastal water resources will be gradually more stressed. This in turn may result in a progressive salinization, which is a widespread and worrying phenomenon worldwide. In this paper, the historical and geographical distribution of peer-review studies focusing on the salinization of water resources along the Italian coasts will be critically discussed.